2022
DOI: 10.1007/s12649-022-01925-4
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Microwave Drying of Acerola Residue: Effects of Pre-treatment and Operating Variables on Main Bioactive Compounds

Abstract: Even though the residue from the processing of acerola (Malpighia emarginata D.C.) has signi cant amounts of vitamin C and other bioactive compounds at the same level as the pulp and the juice of this fruit, it also has a high moisture content level (> 80%). In this work, the drying performance of acerola residue in a microwave oven combined with a vacuum environment was investigated. The effect of pretreatment with ethanol on this drying process was successfully analyzed, together with the in uence of main pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Microwave drying confers better energy usage, a shorter processing time, and a low exposure time of the food to high temperatures, yielding a product with superior quality (Nogueira et al, 2023;Koné et al, 2013). The combination of microwave drying with other techniques, including vacuum application, allows the incorporation of the advantages of the different techniques, minimizing the disadvantages and achieving better quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave drying confers better energy usage, a shorter processing time, and a low exposure time of the food to high temperatures, yielding a product with superior quality (Nogueira et al, 2023;Koné et al, 2013). The combination of microwave drying with other techniques, including vacuum application, allows the incorporation of the advantages of the different techniques, minimizing the disadvantages and achieving better quality.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave-vacuum (MWV) drying combines heat transfer via microwave and decreased pressure. Therefore, this technology can improve energy efficiency and product quality (Nogueira et al, 2023;Corrêa et al, 2011;Costa et al, 2021). Studies have revealed that MWV drying is suitable for drying temperature-sensitive products, including biopharmaceuticals (Alex et al, 2018) and bioactive compounds (Wojdyło, Figiel, & Oszmiański, 2009) such as FOS.…”
Section: Introductionmentioning
confidence: 99%
“…Most acerola production is linked to agribusinesses that produce various products, such as juice, jelly, compote, and especially frozen pulp. The fruit is nutritious, with a high vitamin C content, has strong antioxidant activity, and is a low‐calorie food (da Cruz et al, 2019; Nogueira et al, 2023; Sousa et al, 2011). According to Chang et al (2019), considerable quantities of vitamin C and phenolic compounds in acerola exceed that found in other fruits typically viewed as excellent sources of these compounds, such as grapes, açaí, strawberry, and mango.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, these unconventional fractions of fruits and vegetables are even richer in nutrients than their conventional parts (Aiolfi & Basso, 2013; Carvalho Gualberto et al, 2021). In the case of acerola, processing the fruit generates a residue that consists basically of the seeds, bagasse, and peels, from which new products may be derived due to a composition that is rich in ascorbic acid, phenolic compounds, flavonoids, anthocyanins, and organic acids (do Carmo et al, 2018; Nogueira et al, 2023; Reinaldo et al, 2021). Utilizing the residue also helps alleviate an environmental problem, considering the polluting potential of this material (Cunha et al, 2016; Nóbrega et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation